2019
DOI: 10.1002/jcp.28645
|View full text |Cite
|
Sign up to set email alerts
|

RGS1 silencing inhibits the inflammatory response and angiogenesis in rheumatoid arthritis rats through the inactivation of Toll‐like receptor signaling pathway

Abstract: Emerging evidence shows that rheumatoid arthritis (RA) progression can be induced by the activation of Toll-like receptor (TLR) signaling pathway. Regulator of G-protein signaling 1 (RGS1) is observed to be a candidate biomarker for arthritis. Accordingly, the present study aims to determine the potential effects of RGS1 mediating TLR on RA. A rat model of collagen-induced arthritis (CIA) was established to mimic the features of RA by injection of bovine type II collagen. The rats with CIA were treated with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Emerging evidence shows that the activation of Toll-like receptor signaling pathway can initiate the perpetual cycle of in ammation in the arterial wall and the joint synovium in patients with RA [103]. It is demonstrated that functional suppression of RGS1 inhibits the in ammatory response and angiogenesis by inactivating the TLR signaling pathway in rats with collagen induced arthritis (CIA) [104]. Above investigations improved that the e cacy of ELP against RA via those in ammation associated with pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Emerging evidence shows that the activation of Toll-like receptor signaling pathway can initiate the perpetual cycle of in ammation in the arterial wall and the joint synovium in patients with RA [103]. It is demonstrated that functional suppression of RGS1 inhibits the in ammatory response and angiogenesis by inactivating the TLR signaling pathway in rats with collagen induced arthritis (CIA) [104]. Above investigations improved that the e cacy of ELP against RA via those in ammation associated with pathway.…”
Section: Discussionmentioning
confidence: 98%
“…In the heart, RGS2 has been involved in the control of Gs signaling and cAMP production after β-AR stimulation [30]. RGS1 has been related to the control of in ammation and the immune response [31,32]. The stressinduced alteration in the expression of these genes depends on an active β 2 -AR, since it is unaltered in the group treated with ICI118,551.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that downregulation of Rgs1 suppressed TLR signaling, thereby reducing serum concentration of proinflammatory cytokines and suppressing inflammation in rats with rheumatoid arthritis, which is consistent with our results in OGD/R-triggered hippocampal neuronal injury. 24 Of note, inhibiting miR-27a-3p expression following Rgs1 silencing reverted the protective properties of Rgs1 silencing, further indicating that Rgs1 is a direct target of miR-27a-3p. A single miRNA may target multiple mRNAs and one mRNA may be targeted by multiple miRNAs, 12 our data imply that the anti-inflammatory as well as anti-apoptotic properties of miR-27a-3p are at least in part mediated through targeting Rgs1.…”
Section: Dovepressmentioning
confidence: 96%
“…23 In addition, Rgs1 silencing was shown to suppress inflammatory responses by inactivating TLR4 signaling and reducing the quantities of pro-inflammatory factors like TNF-α, IL-1β, and IL-17 in rheumatoid arthritis rat models. 24 However, the role of Rgs1 in ischemic stroke has not been established.…”
Section: Introductionmentioning
confidence: 99%